Exploring the association of mindfulness, confidence, competitive state anxiety, and attention control in soccer penalty shootouts - Shi, L.; Jing, L.; Wang, H.; Liu, Y. (Frontiers in Psychology, 2024)
Introduction: Penalty shootouts are a pivotal factor influencing outcomes in soccer matches. Soccer players face the challenge of overcoming physical fatigue and psychological pressure when taking penalty kicks. Instances of low confidence and competitive state anxiety during matches exacerbate the detrimental impact on attention control, particularly in non-target defined features, leading to suboptimal performance during penalty kicks.